Co‐formulation of ketoprofen with tulathromycin alters pharmacokinetic and pharmacodynamic profile of ketoprofen in cattle. Issue 1 (13th August 2021) - De Koster, Jenne; Boucher, Joseph F.; Tena, Jezaniah‐Kira; Gehring, Ronette; Stegemann, Michael R.
Abstract: The current studies aimed to evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) profile and to establish a PK‐PD model for ketoprofen in a new fixed combination product containing tulathromycin (2.5 mg/kg) and ketoprofen (3 mg/kg) to treat bovine respiratory disease associated with pyrexia in cattle. Firstly, the effect of different ketoprofen doses as mono‐substance (1, 3, and 6 mg/kg subcutaneous) on lipopolysaccharide‐induced fever was evaluated which indicated that rectal temperature reduction lasted longer in the calves receiving 3 and 6 mg/kg ketoprofen. Secondly, the PK profile of the combination product was compared with mono‐substance products (3 mg/kg subcutaneous and intramuscular). The PK profile of ketoprofen in the combination product was characterized by longer t 1/2, lower C max and increased AUC in comparison with mono‐substance products. Due to prolonged ketoprofen exposure in the combination product, the pyrexia reducing effect of the combination product lasted longer in a second lipopolysaccharide challenge study in comparison with mono‐substance products. Finally, a PK‐PD model for the anti‐pyretic effect of ketoprofen was developed based on the data from the different studies. The PK‐PD model eliminated the need for additional animal experiments and indicated that a 3 mg/kg ketoprofen dose in the combination product provided optimal efficacy.